Ammi Visnaga – A Potential Drug in Field of Homoeopathy (Homoeopathy for All, 2024)
Ammi visnaga, also known as  khella, has long been used in  numerous medicinal systems due to  its therapeutic characteristics. Ammi  visnaga has acquired popularity in  homeopathy due to its capacity to  treat a variety of ailments such as  respiratory disorders, cardiovascular  troubles, and urinary tract problems.  The purpose of this review is to  investigate the pharmacological  qualities and clinical evidence that  support the use of Ammi visnaga in  homeopathic practice. This research  examines the pharmacological  activities, traditional usage, and  therapeutic studies of Ammi visnaga  based on current literature. It also  highlights the challenges and  potential directions for study in this  field. Overall, this analysis sheds  light on the therapeutic potential of  Ammi visnaga in homeopathy and  recommends areas for additional  inquiry.
Keywords: Ammi visnaga; Homoe opathy; Therapuetic; Research